Bringing Oceanography into the Canadian University Classroom - Mills, Eric (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1994)
ABSTRACTThe University of British Columbia's Institute of Oceanography, established in 1949, inaugurated graduate education in oceanography in Canada. It is a rare example of federal government involvement in the content ofhigher education. In the face of competition from McGill and Dalhousie, UBC's success was due to the need for new personnel in oceanography after World War Two, to the presence of the Pacific Oceanographic Group under J.P. Tully nearby in Nanaimo, to Canadian interest in defence during the Cold War and in Arctic development, and to the postwar growth and success of UBC under its president, N.A.M. MacKenzie. UBC exploited the interest of the Canadian Joint Committee on Oceanography, made up of senior civil servants, in physical oceanography to get support for its endeavour. By contrast, Dalhousie, which attempted to base a graduate programme upon bacteriology, failed to find a federal government patron until oceanography expanded further in the late 1950s.